A Pragmatic Study of Bullying in “An American Girl: Chrissa Stands Strong” Movie - Mahdi, Duaa Abd Al-Haleem; Burhanuddin, Israa (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
This study explores the phenomenon of bullying as a prominent sociocultural element within the American film "An American Girl: Chrissa Stands Strong" serve the dual purpose of providing amusement to audiences while also conveying messages of communication, morality, culture, society, and education. In addition to that, bullying remains a widespread problem within the educational institutions. Students, especially those with special cases are constant victims of bullying. The data will be subjected to analysis based on pragmatic theories, such as speech acts and strategies of impoliteness. The questions that the paper tries to answer are: what are the types of verbal bullying and its directness, what are the types of speech acts, what are the illocutionary acts and the directness of speech acts, and what are the impoliteness strategies? This study aims to identify the types and directness of verbal bullying, investigate the types of speech acts in the selected data whether it is used directly or indirectly, identifying the illocutionary acts, and investigating the impoliteness strategies and it is sub-types in "An American Girl: Chrissa Stands Strong" movie. Working on these aims, it is hypothesized that direct verbal bullying of verbal abuse is the predominant type, all the types of speech acts are employed by bullies, the impoliteness strategies are used equally. The study's findings indicate that the predominant kind of bullying observed is direct verbal bullying, characterized by instances of verbal abuse and name-calling. The direct expressive speech acts of mocking/taunting are widely used by girls in "An American Girl: Chrissa Stands Strong" movie. Positive impoliteness strategy is the most frequent strategy.